A Novel Virtual Reality-Based Training Protocol for the Enhancement of the “Mental Frame Syncing” in Individuals with Alzheimer's Disease: A Development-of-Concept Trial - Serino, Silvia; Pedroli, Elisa; Tuena, Cosimo; De Leo, Gianluca; Stramba-Badiale, Marco; Goulene, Karine; Mariotti, Noemi G.; Riva, Giuseppe (Frontiers in Aging Neuroscience, 2017)
A growing body of evidence suggests that people with Alzheimer’s Disease (AD) show compromised spatial abilities. In addition, there exists from the earliest stages of AD a specific impairment in “mental frame syncing,” which is the ability to synchronize an allocentric viewpoint-independent representation (including object-to-object information) with an egocentric one by computing the bearing of each relevant "object" in the environment in relation to the stored heading in space (i.e., information about our viewpoint contained in the allocentric viewpoint-dependent representation). The main objective of this development-of-concept trial was to evaluate the efficacy of a novel VR-based training protocol focused on the enhancement of the “mental frame syncing” of the different spatial representations in subjects with AD. We recruited 20 individuals with AD who were randomly assigned to either “VR-based training” or “Control Group.” Moreover, eight cognitively healthy elderly individuals were recruited to participate in the VR-based training in order to have a different comparison group. Based on a neuropsychological assessment, our results indicated a significant improvement in long-term spatial memory after the VR-based training for patients with AD; this means that transference of improvements from the VR-based training to more general aspects of spatial cognition was observed. Interestingly, there was also a significant effect of VR-based training on executive functioning for cognitively healthy elderly individuals. In sum, VR could be considered as an advanced embodied tool suitable for treating spatial recall impairments.